Upper limb movement quality measures: comparing IMUs and optical motion capture in stroke patients performing a drinking task - Unger, T.; de Sousa Ribeiro, R.; Mokni, M.; Weikert, T.; Pohl, J.; Schwarz, A.; Held, J.P.O.; Sauerzopf, L.; Kühnis, B.; Gavagnin, E.; Luft, A.R.; Gassert, R.; et al. (Frontiers in Digital Health, 2024)
Introduction Clinical assessment of upper limb sensorimotor function post-stroke is often constrained by low sensitivity and limited information on movement quality. To address this gap, recent studies proposed a standardized instrumented drinking task, as a representative daily activity combining different components of functional arm use. Although kinematic movement quality measures for this task are well-established, and optical motion capture (OMC) has proven effective in their measurement, its clinical application remains limited. Inertial Measurement Units (IMUs) emerge as a promising low-cost and user-friendly alternative, yet their validity and clinical relevance compared to the gold standard OMC need investigation. Method In this study, we conducted a measurement system comparison between IMUs and OMC, analyzing 15 established movement quality measures in 15 mild and moderate stroke patients performing the drinking task, using five IMUs placed on each wrist, upper arm, and trunk. Results Our findings revealed strong agreement between the systems, with 12 out of 15 measures demonstrating clinical applicability, evidenced by Limits of Agreement (LoA) below the Minimum Clinically Important Differences (MCID) for each measure. Discussion These results are promising, suggesting the clinical applicability of IMUs in quantifying movement quality for mildly and moderately impaired stroke patients performing the drinking task.